Effect of ESG Trends on Share Prices in Banking Sector - Novikova Polina; Brazhnikova Valeriya; Mishin Andrey (Вестник Кемеровского государственного университета. Серия: политические, социологические и экономические науки)
ESG stands for Environment, Society, and Governance as three crucial criteria considered by socially conscious investors. Economic entities have to adapt to the current global trends in sustainable development thatminimize environmental damage. Banks introduce ESG trends to increase the investment attractiveness of their shares. Before making important decisions, investors take into account the ESG policy of the bank and its sustainable development strategy. The authors studied the effect of ESG policy on the share prices of Russian banks, depending on the fluctuations in the share price of the Moscow Stock Exchange. By reviewing the theory of ESG transformation in modern economy, they identified the correlations between the new ESG policy and the share prices for three largest Russian banks, i.e., SberBank, VTB Bank, and Gazprombank. The logical, structural, and correlation analyses made it possible to determine the expediency of introducing ESG trends in the domestic banking sector. The ESG trends introduced by the three banks appeared to exercise no effect on the domestic market value of their shares. The sustainable development policy demonstrated negligible impact on the value of securities of credit institutions on the Russian stock market. However, the ESG paradigm offerssome economic benefits to organizations and society.